Gut dysbiosis in cutaneous T‐cell lymphoma is characterized by shifts in relative abundances of specific bacterial taxa and decreased diversity in more advanced disease. (19th April 2022) - Hooper, M.J.; LeWitt, T.M.; Pang, Y.; Veon, F.L.; Chlipala, G.E.; Feferman, L.; Green, S.J.; Sweeney, D.; Bagnowski, K.T.; Burns, M.B.; Seed, P.C.; Choi, J.; et al.
Abstract: Background: Cutaneous T‐cell lymphoma (CTCL) patients often suffer from recurrent skin infections and profound immune dysregulation in advanced disease. The gut microbiome has been recognized to influence cancers and cutaneous conditions; however, it has not yet been studied in CTCL. Objectives: To investigate the gut microbiome in patients with CTCL and in healthy controls. Methods: A case‐control study was conducted between January 2019 and November 2020 at Northwestern's busy multidisciplinary CTCL clinic (Chicago, Illinois, USA) utilizing 16S ribosomal RNA gene amplicon sequencing and bioinformatics analyses to characterize the microbiota present in fecal samples of CTCL patients ( n  = 38) and age‐matched healthy controls ( n  = 13) from the same geographical region. Results: Gut microbial α‐diversity trended lower in patients with CTCL and was significantly lower in patients with advanced CTCL relative to controls ( P  = 0.015). No differences in β‐diversity were identified. Specific taxa were significantly reduced in patient samples; significance was determined using adjusted P ‐values ( q ‐values) that accounted for a false discovery rate threshold of 0.05. Significantly reduced taxa in patient samples included the phylum Actinobacteria ( q  = 0.0002), classes Coriobacteriia ( q  = 0.002) and Actinobacteria ( q  = 0.03), order Coriobacteriales ( q  = 0.003), and genus Anaerotruncus ( q  = 0.01). The families Eggerthellaceae ( q  = 0.0007) and Lactobacillaceae ( q  = 0.02) were significantly reduced in patients with high skin disease burden. Conclusions: Gut dysbiosis can be seen in patients with CTCL compared to healthy controls and is pronounced in more advanced CTCL. The taxonomic shifts associated with CTCL are similar to those previously reported in atopic dermatitis and opposite those of psoriasis, suggesting microbial parallels to the immune profile and skin barrier differences between these conditions. These findings may suggest new microbial disease biomarkers and reveal a new angle for intervention.